CO 2 photoreduction on mixed Ti/Zr-MOF-525: bicarbonate as the active intermediate and the role of Ti substitution - Thanyaporn Puengpoka; Jirapat Santatiwongchai; Warot Chotpatiwetchkul; Sareeya Bureekaew; Muhammad Saleh; Anchalee Junkaew; Sarawoot Impeng (Physical Chemistry Chemical Physics, 2026)
reduction and controlling product selectivity by tailoring the metal node environments.
Keywords: Advanced Photocatalysis Techniques; Metal-Organic Frameworks: Synthesis and Applications; Carbon dioxide utilization in catalysis